ChatGPT's Impact on Students Creativity and Academic Performance - Ahmad, MD. Zishan; Tamang, Nikita; Shrestha, Milan; Khatri, Komal; Karki, Jenish Jung; Acharya, Niraj; Parajuli, Suman kamal (International Journal of Humanities, Education, and Social Sciences, 2025)
This study explores the impact of ChatGPT on students' creativity and academic performance, focusing on their perceptions and gender differences. This study adopts a quantitative research approach, gathering data from 190 participants. The data were analyzed using statistical methods, including mean, correlation, t-tests, and regression, to explore the relationships and impacts of ChatGPT on creativity and academic performance. Findings indicate that ChatGPT is broadly recognized as an effective academic tool, appreciated for its ease of use and its role in enhancing academic work. It supports creativity by facilitating brainstorming and generating innovative ideas, although its contribution to creative problem-solving is moderate. In terms of academic performance, ChatGPT aids significantly in saving time and improving clarity in learning. Strong positive correlations were found between ChatGPT usage, creativity, and academic performance. No significant gender differences were observed in perception or usage, confirming its broad applicability, while regression analysis highlighted its substantial contribution to both domains.